2021
DOI: 10.1007/s13318-021-00742-9
|View full text |Cite
|
Sign up to set email alerts
|

A Randomised Study to Investigate the Nicotine Pharmacokinetics of Oral Nicotine Pouches and a Combustible Cigarette

Abstract: Background and Objectives Nicotine pouches (NPs) are a relatively new type of oral smokeless tobacco-free nicotine product. Currently, few data are available on the nicotine pharmacokinetics or subjective effects of NP use. The objective of this study was to determine and compare the pharmacokinetics of nicotine absorption into the blood from different NP variants and a combustible cigarette. Methods In a randomised, controlled, crossover clinical study, nicotine pharmacokinetics and subjective effects were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 40 publications
4
27
0
3
Order By: Relevance
“…Thus, it is di cult to draw parallels to other clinical studies with different experimental setup, or actual use. A study utilizing the same usage time and dry and moist NPs with labeled nicotine strengths of 6-10 mg, found similar C max concentrations to our study (11.9-18.4 ng/mL) [17]. The study conditions used herein, where use of one pouch for 60 min is followed by ve hours of abstinence, are unlikely to re ect consumers actual usage patterns.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Thus, it is di cult to draw parallels to other clinical studies with different experimental setup, or actual use. A study utilizing the same usage time and dry and moist NPs with labeled nicotine strengths of 6-10 mg, found similar C max concentrations to our study (11.9-18.4 ng/mL) [17]. The study conditions used herein, where use of one pouch for 60 min is followed by ve hours of abstinence, are unlikely to re ect consumers actual usage patterns.…”
Section: Discussionsupporting
confidence: 71%
“…A study determining the PK-pro les of NPs from several different manufacturers showed that the nicotine content of a NP gives little information on its nicotine delivery in terms of C max and AUC 0-6h [17]. In line with these ndings, the two product types studied herein contained 9 mg (NP moist varieties) and 6 mg (NP dry varieties) nicotine and showed similar values for C max and AUC inf .…”
Section: Discussionsupporting
confidence: 56%
“…The mechanisms behind the strong association between snus and successful quits are not well understood. The nicotine content and duration of use of snus may provide nicotine in an amount that is similar to cigarette smoking, avoiding or reducing nicotine withdrawal symptoms when quitting cigarettes [41]. There may also be social and cultural expectations towards the use of snus that help fill the gap from the habit of smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Recent surveys of retail sales [17] and product use [16] show that NPs are gaining popularity in the United States, and some authors have suggested that they may form part of a THR approach [23]. To date, however, there are few data available on these relatively new products [14,15,21,22,[73][74][75][76][77][78].…”
Section: Overviewmentioning
confidence: 99%